2021
DOI: 10.1590/1678-7757-2021-0329
|View full text |Cite
|
Sign up to set email alerts
|

A standardized extract of Centella asiatica (ECa 233) prevents temporomandibular joint osteoarthritis by modulating the expression of local inflammatory mediators in mice

Abstract: A standardized extract of Centella asiatica (ECa 233) prevents temporomandibular joint osteoarthritis by modulating the expression of local inflammatory mediators in mice Objectives: To investigate the effect of a standardized extract of Centella asiatica (ECa 233), which has anti-inflammatory properties, on the local expression of the transient receptor potential vanilloid 1 (TRPV1), the acidsensing ion channel subunit 3 (ASIC3), and the calcitonin gene-related peptide (CGRP) in the temporomandibular joint (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Further, some studies have investigated the anti-inflammatory activities of C. asiatica extract in acute inflammatory pain such as in osteoarthritis of knee joints 13 . Recently, our group reported the anti-inflammatory activities of C. asiatica extract in a mouse model of acute temporomandibular joint osteoarthritis in which ECa 233 could inhibit pathogenesis in the affected joint by modulating the local expression of transient receptor potential vanilloid 1 (TRPV1) and acid-sensing ion channel subunit 3 (ASIC3) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, some studies have investigated the anti-inflammatory activities of C. asiatica extract in acute inflammatory pain such as in osteoarthritis of knee joints 13 . Recently, our group reported the anti-inflammatory activities of C. asiatica extract in a mouse model of acute temporomandibular joint osteoarthritis in which ECa 233 could inhibit pathogenesis in the affected joint by modulating the local expression of transient receptor potential vanilloid 1 (TRPV1) and acid-sensing ion channel subunit 3 (ASIC3) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…ASICs are a subdivision of the Degenerin/epithelial Na + channels (ENaC/DEG) superfamily, primarily distributed in the spinal dorsal root ganglion (DRG) and peripheral nerves of the spinal cord, and are most sensitive to pH changes [ 51 ]. Specifically, ASIC3, which exists in chondrocytes, participates in the manifestation and development of OA and regulates pain response and chondrocyte differentiation and metabolism [ 52 , 53 ]. Some studies reported that peripheral inflammation could up-regulate ASIC3 expression in the DRG, indicating that ASIC3 plays a significant role in pain transmission [ 54 , 55 ].…”
Section: Literature Selection Methodsmentioning
confidence: 99%
“…Various pharmacological activities, including anti‐inflammatory [9, 10], antioxidant [11, 12], antibacterial [13, 14], wound‐healing promotion [15–17], and anti‐scarring [18], have been found in CHA. Sanjin Pian containing CHA is an effective drug for the treatment of urinary tract infections [19].…”
Section: Introductionmentioning
confidence: 99%